ECOLINGUISTIC “WATER” IN TOBA BATAK LANGUAGE COMMUNITY - Tarida Alvina Simanjuntak (BASIS (Bahasa dan Sastra Inggris), 2019)
Ecolinguistics is an interdisciplinary study that looks at the link between ecology and linguistics. This study involves other studies, including sociology, anthropology, psychology, and political science. Socio-ecological aspects also greatly affect the maintenance, balance, and environmental inheritance of future generations. These local ecological wisdoms need to be included in a healthy and green environmental discourse (green speak). Knowledge about natural entities for millennial generation has begun to decrease due to the influence of digital technology which is very large. This can also lead to environmental damage and can also damage language by not understanding the cultural functions of the ecolexicon. The amount of Eco lexicon shifting ‘water’ causes millennial generation to no longer know the use of these words in Toba Batak culture. Changes in the lifestyle of the Toba Batak millennial generation have changed considerably and pay less attention to the natural cultural functions. The method used in this study is observation, interviews and qualitative descriptive. This study describes the fact that many natural ecolexics are not recognized anymore and even almost extinct in the Batak Toba community (rootlessness), some of which are mabakbak (flowing tears), bibis (flowing from a container fullness, lungkis (flowing smoothly) and then elaborated in the discussion.